2019
DOI: 10.33945/sami/pcbr.2019.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The bioactivities of the neem (seeds and leaves) against Callosobruchus maculatus on a Vigna Subterranean L.

Abstract: This research reports the novel bioactivities of neem leaves powder, neem leaves concentrate, neem seeds powder and neem seeds oil against the weevil (Callosobruchus maculatus) on bambara groundnut. The leaves were ground, crushed and subjected to ethanol to get the concentrate. While the seeds were dried under shade for one week, ground into fine particles. Cold bulk extraction was then used to obtain the neem seeds oil. The mortality count of Callosobruchus maculatus (C. maculatus) was studied by exposing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Additionally, no seed damage was recorded by V. unguiculata in cowpea seeds treated with the highest dosage of C. colocynthis (Nzelu and Okonkwo, 2016). Asemave and Anure (2019) indicated that Bambara groundnut treated with neem seed oil at rates of 1.0 and 0.5 mL/10 g exhibited 0% weight loss. In addition, the results of seed damage showed that neem seed extract gave the lowest seed damage at 0.5 and 1.0 mL/10 g. Neem seed oil at 5, 7.5, and 10 mL/kg was more effective in reducing weight loss by the pulse beetle C. chinensis in stored black gram grains and significantly reduced adult emergence (Pathania et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, no seed damage was recorded by V. unguiculata in cowpea seeds treated with the highest dosage of C. colocynthis (Nzelu and Okonkwo, 2016). Asemave and Anure (2019) indicated that Bambara groundnut treated with neem seed oil at rates of 1.0 and 0.5 mL/10 g exhibited 0% weight loss. In addition, the results of seed damage showed that neem seed extract gave the lowest seed damage at 0.5 and 1.0 mL/10 g. Neem seed oil at 5, 7.5, and 10 mL/kg was more effective in reducing weight loss by the pulse beetle C. chinensis in stored black gram grains and significantly reduced adult emergence (Pathania et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The filtrate was poured into beaker and was allowed for 2 days for the ethanol to evaporate. (Asemave and Anure, 2019) [85] .…”
Section: Extraction Of the Plant Extractmentioning
confidence: 99%
“…In such a manner, the overdependence on petroleum (a finite resource) for myriads of raw materials for our industries and allied purposes can be substantially shifted to renewable source. In view of this, there has been high quantum of surge about sourcing/ deriving chemicals from plant-based origin [2][3][4][5][6][7][8][9]. More recently, Green Chemistry has also underscored the need for sustainable development, which partly provides the use of benign and renewable materials instead petrochemicals [10].…”
Section: Introductionmentioning
confidence: 99%